Agency under constraint: Adolescent accounts of pregnancy and motherhood in informal settlements in South Africa. Issue 9 (2nd September 2022) - Gillespie, Bronwen; Allen, Haddijatou; Pritchard, Matthew; Soma-Pillay, Priya; Balen, Julie; Anumba, Dilly
Abstract : Progress in adolescent sexual and reproductive health (SRH) remains unequal: adolescent pregnancies are more likely to occur in marginalised communities, or in very poor households. This study aimed to comprehend from adolescents' own perspectives, the circumstances of falling pregnant and coping with motherhood in informal settlements in South Africa, to better understand the SRH challenges adolescents in these settings may face. A qualitative study was carried out over a two-month period in 2019 to analyse the perceptions held by adolescents in informal settlements served by four community-level clinics in the adjacent township. We found that adolescents face overlapping barriers in seeking to avoid unintended pregnancy in informal settlements. Once they become mothers, their trajectory is limited by the resources and support available from their own parents, particularly their mothers, and to a lesser extent, their partners. We draw on the concept of agency to examine their accounts and to highlight the importance of addressing broader contextual constraints.